Spatiality, Temporality and Ontology: Constraints for the Restitution of Indigenous Peoples’ Territorial Rights in Colombia (Alternautas, 2022)
In this article, three limitations to how ethnic land restitution has been carried out in Colombia to date are discussed. The specific restrictions that I mention are related to 1) temporality, 2) spatiality, and 3) to the ontology of the idea of reparations concerning indigenous peoples’ territorial rights. These findings result from fieldwork conducted in 2017 and 2018 in the Aponte indigenous reserve of the Inga people. The first section of the article briefly describes the history and functioning of Act 1448 of 2011, known in Colombia as the Law on Victims and Land Restitution. In the second section, I describe the case of the Inga people in Aponte, located in the department of Nariño, in southern Colombia. In the third section, I discuss the three limitations mentioned above regarding the land restitution process, followed by a conclusion.